Perancangan dan Evaluasi Usability UI/UX Aplikasi Manajemen Produksi Budidaya Sarang Burung Walet Menggunakan Metode Design Thinking (Studi Kasus: CV Mega Walet Sejahtera) - Ivanka A. J. Pasanda; Mans L. Mananohas; Stephano C. W. Ngangi (INTECH, 2026)
CV Mega Walet Sejahtera still manages the recording and production management process of edible bird’s nest cultivation manually using Microsoft Excel and separate communication media, causing delays in reporting, difficulties in data recapitulation, and inefficient production monitoring and evaluation processes. This study aims to design and evaluate the usability of a UI/UX prototype for an edible bird’s nest production management application using the Design Thinking method. The research applied a mixed methods approach through interviews, observations, usability testing, and the System Usability Scale (SUS) questionnaire. The design process was carried out through the stages of empathize, define, ideate, prototype, and testing. The application prototype was designed using Figma and tested using the Maze platform involving seven respondents consisting of the business owner and field workers. The results showed that the application prototype achieved a very good level of usability based on Nielsen’s five usability attributes, namely learnability, efficiency, memorability, errors, and satisfaction. The SUS testing produced an average score of 87.7, which falls into the best imaginable category and is considered acceptable. In addition, the MAUS testing results obtained scores of 93 for the owner and 89 for the workers. These findings indicate that the Design Thinking method successfully produced a UI/UX design that meets user needs and supports more effective and user-friendly production recording, reporting, and monitoring processes.